Social capital and fertility intentions: The case of Italy, Bulgaria, and West Germany - Paola Di Giulio; Christoph Bühler; Andreas Ette; Romina Fraboni; Kerstin Ruckdeschel (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2012)
Despite the many differences that exist between Italy, Bulgaria, and Germany, the three countries are among those with the lowest fertility rates in Europe. However, they differ in the level of public support for families and the role of informal supportive networks in daily life. Italy and Bulgaria, on the one hand, share very low levels of public support. In both countries, consequently, informal supportive networks based on family relationships and kinship have a strong tradition and a high relevance for getting things done. In Germany, however, support by family policy is much stronger and the importance of such supportive networks is weaker. The paper addresses the question whether these different constellations of public and informal social support have an impact on reproductive decision-making. In particular, it concentrates on the impact of supportive networks on intentions to have a second child. Analyses based on data from the 'Generations and Gender Programme', a comparative survey that was conducted recently in all three countries, provide mixed results. While there is a significant influence of access to informal support on the intention to have a second child in Bulgaria and no significant effect in West Germany, findings for Italy obviously contradict theoretical propositions and suggest that future analysis takes more comprehensive account of the work strategy of the mothers in the context of the current Italian labour market characteristics.
Keywords: 300; Social capital; fertility; fertility intentions; informal help; informal support; Social Capital; Fertilität; Soziales Netzwerk; Familienplanung; Italien; Bulgarien; Alte Bundesländer